2022
DOI: 10.1038/s41524-022-00825-4
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of stable Li-Sn compounds: boosting ab initio searches with neural network potentials

Abstract: The Li-Sn binary system has been the focus of extensive research because it features Li-rich alloys with potential applications as battery anodes. Our present re-examination of the binary system with a combination of machine learning and ab initio methods has allowed us to screen a vast configuration space and uncover a number of overlooked thermodynamically stable alloys. At ambient pressure, our evolutionary searches identified an additional stable Li3Sn phase with a large BCC-based hR48 structure and a poss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 114 publications
0
26
0
Order By: Relevance
“…50,51 The slight overbinding of bcc-Li with respect to molecular Li 2 by 0.03 eV per Li in our default DFT approximation would result in a small shift in the boundary, D log 10 ðP=P 0 Þ % 0:03=0:07 log 10 ðeÞ % 0.19 at 800 K. Assessment of discrepancies between DFT and experiment for solid state phases is more challenging because measurements are usually conducted at elevated temperatures. 52 The typical differences of up to B20 meV per atom between DFT flavors in the calculation of relative energies 3,12,52 and the neglected configurational entropy term of similar values (Fig. 3(b)) could be amplified to a sizable 0.2 eV per Li upon rescaling to be per Li atom.…”
Section: (B) the Correction Brings The Free Energy Of Intermediate Ph...mentioning
confidence: 99%
“…50,51 The slight overbinding of bcc-Li with respect to molecular Li 2 by 0.03 eV per Li in our default DFT approximation would result in a small shift in the boundary, D log 10 ðP=P 0 Þ % 0:03=0:07 log 10 ðeÞ % 0.19 at 800 K. Assessment of discrepancies between DFT and experiment for solid state phases is more challenging because measurements are usually conducted at elevated temperatures. 52 The typical differences of up to B20 meV per atom between DFT flavors in the calculation of relative energies 3,12,52 and the neglected configurational entropy term of similar values (Fig. 3(b)) could be amplified to a sizable 0.2 eV per Li upon rescaling to be per Li atom.…”
Section: (B) the Correction Brings The Free Energy Of Intermediate Ph...mentioning
confidence: 99%
“…Unfortunately, the high cost of ab initio calculations limits the scope of unconstrained searches. Evaluation of structure stability with less expensive and fairly accurate machine learning potentials (MLPs) has shown great promise for accelerating ab initio searches [16] but successful predictions of stable compounds remain scarce [17][18][19][20]. In particular, our recent re-examination of the Li-Sn binary with a MLP has uncovered several stable alloys with large unit cells not detected in ab initio searches [19].…”
Section: Introductionmentioning
confidence: 99%
“…For NIBs, the peaks of Sn−S and Sn−Se remained after full discharge, and Na−Sn (2.68 Å) indicated that amorphous MSSS would undergo an alloying reaction at low potentials with Na‐ions. [ 25b ] The reaction was also reversible for amorphous MSSS in NIBs, as only two peaks of Sn−S and Sn−Se were observed after full charging, as shown in Figure 5f.…”
Section: Resultsmentioning
confidence: 96%
“…From the reported simulations, the shortest length of Li−Sn can range from 2.5 to 2.61 Å. [ 25 ] Although no significant electron transfer was observed in the XANES spectra, Li x Sn was formed after full discharging. For the fully charged state, the peaks mainly consisted of Sn−S and Sn−Se.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation